Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
7a-3=3-2a
9a-3=3 (add 2a to both sides)
9a=6 (add 3 to both sides)
a=6/9 (divide by 9 to both sides)
9a-3=3 (add 2a to both sides)
9a=6 (add 3 to both sides)
a=6/9 (divide by 9 to both sides)
get all variables (in this case, "a") on one side by adding "2a" to both. this cancels the "-2a". then, combine like terms. also move "-3" to the other side, by adding "3". finally, divide the "6" and "a" by "9" to get variable alone. therefore, "a = 2/3".
7a-3=3-2a
+2a +2a
9a-3=3
+3 +3
9a=6
a=2/3
7a-3=3-2a
+2a +2a
9a-3=3
+3 +3
9a=6
a=2/3
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.